Uso do UV-Vis, capacímetro e condutivímetro, para detecção de adulteração da gasolina - Limeira, Samuel Nunes (2024)
Human beings are in constant search for the development of society, aiming to facilitate work and travel. In this search, fuels have become a fundamental tool for evolution. With the growth of production and the fuel market, some people, whether out of bad faith or due to inadequate storage, caused changes that resulted in these products not complying. Fuel adulteration occurs when its physical chemical properties are modified by the inclusion of a new compound, such as solvents, or by the excess of another fuel already naturally present with the aim of obtaining financial gains. Given this scenario, this study aimed to contri bute to the identification of a possible adulteration of the fuel, specifically gasoline, bringing as its objective a method for the analysis of sensory variables associated with contamination by methanol and water that can be used in other renewable fuels . For this purpose, the UV Vis, conductivity meter and capacitance meter were used, which are relatively simple sensors. The research was carried out in the fuels and lubricants laboratory at the Federal University of Ceará. Following appropriate procedures, samples of type A gasoline were formulated without the addition of anhydrous ethanol, with the addition of contaminants in pre determined percentages, continuing with the reading of the sensors, as well as recording the data. After averaging the results per sample, graphs were created measuring absorbance, conductivity and capacitance in relation to the percentage of impurities. Each sensor, according to its characteristics, has demonstrated effectiveness in detecting different impurities. The conductivi ty meter and capacitance meter showed better performance in detecting methanol in gasoline. On the other hand, the UV Vis sensor showed consistent results for detecting water in gasoline. The results followed a repetitive pattern and it was possible, in th e end, to conclude that there is the possibility of identifying adulteration in gasoline through UV Vis, conductivity meter and capacitance meter.